Bibliometric Analysis of Microcontroller-Based Learning Media (Jurnal Pendidikan Fisika dan Keilmuan (JPFK), 2023)
This study aims to conduct a bibliometric analysis of the research trends of microcontroller-based learning media. This analysis was carried out using VOSViewer software on articles indexed on Google Scholar during the period 2008 to 2024. The results of the analysis show that there are 526 articles discussing the development of microcontroller-based learning media, with the peak of publication occurring in 2023. The study also identified four main clusters in this study, namely "Science and Technology Learning Media," "Physics Learning Media," "Internet and Technology-Based Learning Media," and "Microcontroller Learning Media." Current research trends tend to focus on the integration of advanced technologies such as the Internet, Arduino, and the Internet of Things (IoT) in learning. This study is expected to be a foundation for other researchers in determining research topics related to the development of microcontroller-based learning media.